S-comerce como ferramenta para promover vendas: uma análise do varejo de roupas no Centro Fashion de Fortaleza - Pereira, Antonio Jocélio Alves (2020)
Commercial relations have undergone profound changes over the years. This reinforces that, with the insertion of new technologies, with the advent of computing at popular levels and accessible to practically everyone, they started to use the media and social networks such as Twitter, Facebook, Instagram, LinkedIn, not only to strengthen the relationship, but also to market products and services. This ends up contributing to the online environment, where participants share and seek common experiences, activities and common interests, which are the main source of s-commerce (ZENG et al., 2009; ZORRILLA, 2002; SHIN; PARK; MOON, 2015). This work kept the focus on the popular clothing trade segment, where the digital market is gaining more and more strength. In this context, the present study aimed to analyze how the use of s-commerce can impact sales performance in companies located in the Centro Fashion de Fortaleza, using the models adopted by Longaray et al. (2018) and Lunardi; Dolci; Maçada (2010). A construction that has been initially developed by Lunardi; Dolci; Maçada (2010) and perfected by Longaray et al. (2018), which, the latter, reached the following categories: internal motivations, external motivations and benefits perceived through F-commerce as a tool capable of impacting the performance of Brazilian micro and small companies. The research used quantitative methods, with survey-type research through a structured questionnaire and use of the Likert scale. The data were tabulated in Excel and analyzed using SPSS 20.0. The collection instrument was validated using Cronbach's Alpha and a factor analysis was performed. The results were obtained using descriptive statistics and means comparison tests (non-parametric Mann-Whitney and Kruskal-Wallis tests). The results indicate that among the internal reasons that are leading the entrepreneurs of the Centro Fashion in Fortaleza to use s-commerce in their businesses, the use to improve customer service stands out. Regarding the external reasons for using s-commerce in their businesses, retailers understand that the use is due to the influence of customers and because competitors have also used it. Regarding the benefits obtained by using s-commerce, Centro Fashion retailers understand that s-commerce strongly helps in obtaining new customers and facilitates the obtaining of useful information to the company, both propositions with 78.3%. The study contributes because it is a recent phenomenon, with strong market practice and few academic studies.